115k views
3 votes
If f(x) = 3x + 10 and g(x) = 2x - 4, find (f- g)(x).

User Padi Amu
by
5.6k points

1 Answer

2 votes

Answer:

(f-g)(x)=x+14

Explanation:

Operations with Functions

Given two functions f(x) and g(x), the following operations are defined:

(f+g)(x)=f(x)+g(x)

(f-g)(x)=f(x)-g(x)

(f*g)(x)=f(x)*g(x)

(f/g)(x)=f(x)/g(x)

We have f(x)=3x+10 and g(x)=2x-4. Use the second formula to find

(f-g)(x)=(3x+10)-(2x-4)

Operating:

(f-g)(x)=3x+10-2x+4

Joining like terms:

(f-g)(x)=x+14

User Chuim
by
6.5k points